Digital Transformation of BUMDes Financial Management: The Effectiveness of BUMDes Financial Application Features in Improving the Accuracy and Ease of Financial Reporting for Service and Trade Companies - Najmudin; Nunik Kadarwati; Muhammad Taufiq; Sofiatul Khotimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the effectiveness of digital transformation in improving financial management of Village-Owned Enterprises (BUMDes) through financial applications. Using a qualitative descriptive approach, data were collected via interviews, observations, and document analysis from BUMDes utilizing such applications. Results show these applications enhance efficiency in financial data processing, provide real-time reporting, minimize errors, and improve access to financial information, especially for service and trade units. Despite these benefits, challenges persist, including inadequate infrastructure and limited technological skills. Continued development and support for these applications are crucial to optimize financial management and promote transparency, accountability, and better governance in BUMDes operations.